Prediksi Perubahan Penggunaan Lahan Kota Bukittinggi menggunakan Integrasi Cellular Automata dan Analytical Hierarchy Process - Armensyah, Viery; Iswandi, Iswandi (Lembaga Yasin AlSys, 2025)
Land use change is a strategic issue in managing rapidly growing urban areas, including the city of Bukittinggi. Urbanization, population growth, and infrastructure development have driven the conversion of green spaces into built-up areas, resulting in increased environmental disaster risks and pressure on ecosystems. This study aims to analyze the land cover change patterns in Bukittinggi from 2017 to 2023 and to predict future changes by 2035 through the integration of the Cellular Automata (CA) and Analytical Hierarchy Process (AHP) models. The methodology includes Landsat satellite image classification and spatial analysis using Geographic Information Systems (GIS). The AHP model was applied to assign weights to various factors influencing land use change, such as accessibility, population density, and land use types, which were then integrated into the CA predictive simulation. The results indicate a trend of increasing built-up land and a significant decline in agricultural and forest areas. The integration of CA and AHP models produced more accurate spatial predictions, offering a reliable basis for sustainable spatial planning. These findings contribute significantly to policy-making by supporting the design of urban development strategies that are both adaptive to change and environmentally sustainable.